(untitled) (International Journal of Advanced Digital Systems and Multidisciplinary Studies, 2026)
This paper explores the integration of problem-based learning within the digital transformation of educational frameworks, examining various models, their practical applications, and the resulting educational outcomes. It analyzes how this pedagogical approach, which emphasizes student-centered learning through real-world problems, is being adapted to virtual environments to foster higher-order thinking skills and prepare students for complex, evolving challenges. Specifically, this study investigates how universities are leveraging digital tools to implement ProblemBased Learning in ways that were previously unfeasible in traditional face-to-face settings, thereby enhancing learning engagement and knowledge acquisition. The paper further delves into the challenges and opportunities presented by this digital shift, highlighting how successful implementation requires a deep understanding of both pedagogical principles and technological capabilities to facilitate meaningful learning experiences. This exploration extends to the impact of digital PBL on critical employability skills, such as critical thinking and problem-solving, which are crucial for preparing graduates for dynamic industry needs. Ultimately, the paper aims to delineate a comprehensive understanding of how digitally-transformed PBL not only enhances academic competencies but also cultivates essential professional attributes necessary for navigating the complexities of the modern workforce.